Analisis Pelaporan Kinerja Per Jenis Produk Dalam Rangka Meningkatkan Efisiensi Kebun pada Pusat Penelitian Teh dan Kina, Gambung - Munawar, Aang (STIE Kesatuan, 2000)
This research is aimed at analyzing detil of cost, auditing of cost, determining cost allocation and cost of production, and reporting performance based on the type of product. Teh performance is measured by assessing the deviation among the costs. The result of research has recommended to enhance efficiency of estate crops and use it as a feedback for establishing strategic plan. Keywords: Reporting Performance; Efficiency; Research Center